Transient hyperthermia during oxygenated rewarming of isolated rat livers. (6th November 2019) - von Horn, Charlotte; Minor, Thomas
Summary: Pretransplant machine perfusion of donor grafts has gained clinical appreciation to improve graft function and survival after transplantation. This study was aimed as pilot investigation to evaluate the additive potential of a transient ex vivo heat shock treatment of the isolated organ during machine perfusion to further protect the graft from subsequent reperfusion injury. Rat livers were retrieved after 20 min of cardiac arrest and preserved for 18 h by cold storage in HTK solution. Prior to reperfusion, livers were subjected to 2 h of reconditioning machine perfusion with gradual increase in perfusion temperature up to 35 °C. In half of the livers ( n = 7), a brief hyperthermic impulse (10 min perfusion at 42 °C) was implemented in the machine perfusion period. Functional recovery of the grafts was observed upon normothermic reperfusion in vitro . Induction of heat shock protein 70 was followed on the mRNA and protein level. Chaperone induction by transient hyperthermia was associated with a significant improvement of bile production upon reperfusion and significantly reduced enzyme loss of mitochondrial GLDH. Heat shock treatment further affected pro‐inflammatory upregulation in the graft in significantly reducing gene expression as wells as protein release of TNF‐alpha. It is concluded, that graft conditioning by controlled hyperthermia ex vivo may represent a feasible and useful tool to improve liver recovery after preservation.